2017
DOI: 10.1051/0004-6361/201630272
|View full text |Cite
|
Sign up to set email alerts
|

An in-depth spectroscopic examination of molecular bands from 3D hydrodynamical model atmospheres

Abstract: Context. Tighter constraints on metal-poor stars we observe are needed to better understand the chemical processes of the early Universe. Computing a stellar spectrum in 3D allows one to model complex stellar behaviours, which cannot be replicated in 1D. Aims. We examine the effect that the intrinsic CNO abundances have on a 3D model structure and the resulting 3D spectrum synthesis. Methods. Model atmospheres were computed in 3D for three distinct CNO chemical compositions using the CO 5 BOLD model atmosphere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Molecular features are highly susceptible to 3D effects, with abundance corrections becoming more negative towards lower [Fe/H] that are of the right order of magnitude (0.7 to 1.1 dex) to bring their results into agreement with ours (e.g. Collet et al 2006;Gallagher et al 2017).…”
Section: Discussionsupporting
confidence: 78%
“…Molecular features are highly susceptible to 3D effects, with abundance corrections becoming more negative towards lower [Fe/H] that are of the right order of magnitude (0.7 to 1.1 dex) to bring their results into agreement with ours (e.g. Collet et al 2006;Gallagher et al 2017).…”
Section: Discussionsupporting
confidence: 78%
“…It should also be noted that many improvements regarding the details of abundance analyses (e.g., NLTE, 3D calculations) have been made in the last few years (Gallagher et al 2017;Nordlander et al 2017). However, these are not yet available for many stars, and whatever has been collected from the literature has likely not (yet) benefited from these advances.…”
Section: Guide For Choosing Element Abundance Samples For Model Compamentioning
confidence: 99%
“…The 3D correction has been computed by Asplund & García Pérez (2001) and González Hernández et al (2010) with two different grids of 3D models and their results are in good agreement. For dwarfs and The star BD +44 • 493 is peculiar, it is very C-rich and Gallagher et al (2017) have shown that the carbon abundance affects the molecular equilibria in 3D hydrodynamical models in a much more prominent way than happens in 1D models. Using a C-rich hydrodynamical model atmosphere computed with the CO 5 BOLD code (Freytag et al 2012), we determined that the 3D correction in this case is only -0.3 dex.…”
Section: Be-o Correlationmentioning
confidence: 99%